1998
DOI: 10.1097/00008483-199805000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music on Exercise and Perceived Symptoms in Patients With Chronic Obstructive Pulmonary Disease

Abstract: There were no statistically significant differences observed between treatment conditions for distance walked, perceived dyspnea or ratings of perceived exertion. It should be noted that 60% of the subjects voluntarily commented that they enjoyed listening to music while they exercised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 10 publications
2
11
0
1
Order By: Relevance
“…We did not observe an impact of music on exercise capacity, as was demonstrated previously. 38 Our results are similar to those of another study that evaluated the effect of listening to music in subjects with COPD during a 6-min walk test, 46 even though exercise duration was different. The design of our study, with a similar level of exercise in both sessions and an evaluation of only one session, did not permit us to observe this influence during a long-term period.…”
Section: Discussionsupporting
confidence: 84%
“…We did not observe an impact of music on exercise capacity, as was demonstrated previously. 38 Our results are similar to those of another study that evaluated the effect of listening to music in subjects with COPD during a 6-min walk test, 46 even though exercise duration was different. The design of our study, with a similar level of exercise in both sessions and an evaluation of only one session, did not permit us to observe this influence during a long-term period.…”
Section: Discussionsupporting
confidence: 84%
“…2,3,17,18 Our observations in this study are consistent with those in previous studies that investigated the effect of DAS on dyspneic sensation induced by exercise. 2,17 Thornby et al 17 showed that DAS attenuated treadmill exercise-induced dyspnea.…”
Section: Discussionsupporting
confidence: 92%
“…This phenomenon has not been reported in other studies on the effect of DAS on dyspnea in subjects with COPD. 2,3,17,18 This novel finding suggests that DAS may enable patients with COPD to exercise for longer time periods. Cycle ergometer exercise can more accurately maintain the intensity of exercise load than either treadmill exercise or field walking.…”
Section: Discussionmentioning
confidence: 85%
“…This rationale has been confirmed in research studying respiratory-related evoked potentials in the electroencephalogram, which showed reduced neural processing of respiratory sensations during attentional distraction compared to recruitment of attention conditions [134, 135]. However, research in COPD patients has produced conflicting results, with some studies showing reductions of exertional dyspnea and/or increases in exercise performance during attentional distraction by music [19, 136, 137], whereas other studies failed to observe beneficial effects on dyspnea [138140]. Due to this inconclusive evidence, recent systematic reviews and guidelines do not support the routine use of attentional distraction for COPD [97, 99].…”
Section: Behavioral Medicine Treatmentmentioning
confidence: 99%